Intranasal Delivery and Transfection of mRNA Therapeutics in the Brain Using Cationic Liposomes - Dhaliwal, Harkiranpreet Kaur; Fan, Yingfang; Kim, Jonghan; Amiji, Mansoor M (Molecular pharmaceutics, 2020)
Nucleic acid-based therapeutics, including the use of messenger RNA (mRNA) as a drug molecule, has tremendous potential in the treatment of chronic diseases, such as age-related neurodegenerative diseases. In this study, we have developed a cationic liposomal formulation of mRNA and evaluated the potential of intranasal delivery to the brain in murine model. Preliminary studies in J774A.1 murine macrophages showed GFP expression up to 24 h and stably expressed GFP protein in the cytosol. Upon intranasal administration of GFP-mRNA/cationic liposomes (3 mg/kg dose) in mice, there was significantly higher GFP-mRNA expression in the brain post 24 h as compared to either naked mRNA or the vehicle-treated group. Luciferase mRNA encapsulated in cationic liposomes was used for quantification of mRNA expression distribution in the brain. The results showed increased luciferase activity in the whole brain in a dose-dependent manner. Specifically, the luciferase-mRNA/cationic liposome group (3 mg/kg dose) showed significantly higher luciferase activity in the cortex, striatum, and midbrain regions as compared with the control groups, with minimal systemic exposure. Overall, the results of this study demonstrate the feasibility of brain-specific, nonviral mRNA delivery for the treatment of various neurological disorders.